Skrining Kesehatan dan Tumbuh Kembang Anak Usia Dini Untuk Mewujudkan Generasi Emas Tahun 2045 di TK Aisyiyah Korpri - Sri Ariyanti; Surtikanti Surtikanti; Tri Wahyuni (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
Low awareness of parents and educators on the importance of monitoring children's growth and development and the lack of regular health screening in schools has the potential to cause delays in the detection of developmental disorders. This community service activity aims to improve the early detection of early childhood growth and development through the implementation of health screening at Aisyiyah Bustanul Athfal Korpri Kindergarten, Kubu Raya Regency. This activity supports improving the quality of children's health and efforts to realize Indonesia's Golden Generation 2045. The method of the activity is carried out through three stages, namely preparation, implementation, and evaluation. The implementation of activities includes education to PAUD teachers about monitoring children's growth and development, measuring growth parameters such as weight and height, and developmental screening using the Pre-Screening Developmental Questionnaire (KPSP) through observation and interviews. The results of the activity showed an increase in teachers' understanding with an average pre-test score of 80.25 to 96.80 in the post-test and the availability of initial data on the status of children's growth and development. This activity has implications for knowing the status of children's development early and increasing the capacity of teachers in monitoring children's growth and development.